Biochemical Analysis for the Determination of Renal and Pancreatic Disorders in Dogs - Sharma, Nisha; Shrestha, Mukti N (Nepal Journal of Science and Technology, 2012)
A study was conducted to evaluate the renal and pancreatic disorders in the dogs from September to December 2010. One hundred serum samples were collected from one hundred dogs showing the common signs and symptoms of renal and pancreatic disorders. All the serum samples were analyzed in the Laboratory of the Vet Clinic, Krishnagalli, Lalitpur. The biochemical analysis for kidney function tests was Blood urea nitrogen (BUN) and serum creatinine whereas for pancreatic disorders was alpha amylase test. The result showed the higher prevalence of both renal and pancreatic disorders together (25%) followed by pancreatic disorder which (24%) and renal disorders was (14%). Among breeds, pure breeds were found to have higher prevalence for both renal and pancreatic disorders (25.6%). Mongrels were found to have higher prevalence of pancreatic disorders (50%), and cross breeds had higher prevalence for renal disorders (38 %.) Among the pure breeds, German Shepherd had the higher prevalence. In sexwise distribution, males were more vulnerable than females. In the agewise prevalence, age groups of 5-10 were found to be more vulnerable for renal disorders followed by 10-15 and 0-5 years age group. Similarly, age groups of 10-15 were found to be highly vulnerable for pancreatic disorders followed by 5-10 and 0-5 years age group. This study, showed range value of BUN, Creatinine, and Alpha amylase were found to be 7-227 mg/dl, 0.6-41mg/dl and 112-2686 IU/L respectively. DOI: http://dx.doi.org/10.3126/njst.v12i0.6481 Nepal Journal of Science and Technology 12 (2011) 61-68